RELATIONSHIPS AMONG ORGANIZATIONAL COMMITMENT, KNOWLEDGE SHARING AND EMPLOYEE PERFORMANCE: A REVIEW - Udin, Udin (International Journal of Psychosocial Rehabilitation, 2020)
This paper looks at the relationships among organizational commitment, knowledge sharing and employee performance. This paper uses a literature review analysis to provide insight into the relationship between these variables. Based on the analysis, this paper reveals strong relationships among organizational commitment, sharing of knowledge and employee performance. Highly committed employees are voluntary to improving the organization and sharing of knowledge is the ideal way to do it, since knowledge seems to be the most essential priority in organizations.